Revolution and Counter-Revolution in the Middle East and North Africa. Global Politics, Protesting and Knowledge Production in the Region and Beyond - Paola Rivetti (Coordinamento SIBA, 2021)
This paper discusses the current political phase in South West Asia and North Africa (SWANA) or Middle East and North Africa (MENA) by contextualising it in global politics. First, the transformations of the nation state and neoliberal capitalism are discussed along with the mobilisational strategies shared among social movements in the region, Europe and North America, Africa, and Latin America. Second, the paper discusses how such transnational developments have influenced the scholarship on SWANA/MENA politics, highlighting a number of epistemological breaks in the content and process of knowledge production.